A case report of recurrent spontaneous coronary artery dissection and Takotsubo cardiomyopathy: a treatment dilemma. Issue 1 (10th February 2020) - Ghafoor, Hafiz U; Bose, Abhishek; El-Meligy, Amr; Hannan, Joseph
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is an uncommon cause of acute coronary syndrome in younger females with no pre-existing history of coronary artery disease. Recurrent SCAD is common after a first episode and can involve the same coronary artery or present as a new dissection unrelated to the initial lesion. Current recommendations advise for a conservative approach in the absence of haemodynamic compromise and flow limitations. Conversely, there are no clear guidelines for the management of early recurrent SCAD. Case summary: A 52-year-old woman with history of obesity, asthma, and prediabetes presented with chest pain and electrocardiogram (ECG) showing inferior wall ST-elevation myocardial infarction (STEMI). Coronary angiography revealed proximal right coronary artery (RCA) dissection and distal left anterior descending artery (LAD) dissection, while left ventriculogram showed Takotsubo cardiomyopathy (TC). Angiography revealed no flow limitations so conservative management was pursued. She returned within a couple of days with recurrent chest pain and ECG showing similar findings of inferior STEMI. Repeat angiography confirmed progression of the proximal RCA SCAD with resolution of distal LAD SCAD. Since flow through the distal RCA was still preserved, conservative medical management was continued. She presented a third time for palpitations only and another repeat coronary angiogram showed healing RCA SCAD. Discussion: Management of early recurrent SCAD continues to be a clinical dilemma. In addition, our patient had features of TC which shares a similar clinical risk factor profile with SCAD thus it may be prudent to further investigate for TC in patients presenting with SCAD and have suggestive features of TC on history and echocardiography.